2021
DOI: 10.21203/rs.3.rs-683529/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimized EEG–fNIRS Based Mental Workload Detection Method for Practical Applications

Abstract: Background: Mental workload is a critical consideration in complex man–machine systems design. Among various mental workload detection techniques, multimodal detection techniques integrating EEG and fNIRS signals have attracted considerable attention. However, existing EEG–fNIRS-based mental workload detection methods have certain defects, such as complex signal acquisition channels and low detection accuracy, which restrict their practical application.Method: The signal acquisition configuration was optimized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…It meant that different methods explored distinct information and became complementary to each other thereby improving classification performance. The results agreed with the conclusion in the literature [ 29 , 38 , 39 , 42 ]. The present paper is an advance on previous studies because it generated new knowledge about regional information by comparing the foci of independent types of features.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It meant that different methods explored distinct information and became complementary to each other thereby improving classification performance. The results agreed with the conclusion in the literature [ 29 , 38 , 39 , 42 ]. The present paper is an advance on previous studies because it generated new knowledge about regional information by comparing the foci of independent types of features.…”
Section: Discussionsupporting
confidence: 92%
“…Brouwer et al [ 33 ] found the alpha power of the midline parietal (Pz) region in EEG recordings significantly decreased with memory load, effectively distinguishing 2-back from 0-back. Chu et al [ 39 ] stated that the alpha-power of O1 indicated differences between multi-level workloads. Regarding fNIRS, the prefrontal areas were well-accepted for measuring variations in mental workload [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%